Hydrology Monitoring In Conjunction With The Condition Of Coral Reefs In The Waters of Talise Island, North Sulawesi - Jemmy Souhoka; Simon I Patty (Jurnal Ilmiah PLATAX, 2013)
ABSTRACT Monitoring hydrologic conditions in the waters of Talise Island, North Sulawesi has been conducted in July and October 2009. The result showed that the temperature ranged from 28.85 to 30.70 °C, salinity between 33.0 to 34.0 o/oo, the turbidity up to 24 m, dissolved oxygen between 5.05 to 6.01 ppm, phosphate between 0.015 to 0.056 mg/l, nitrate between 0.003 to 0.020 mg/l and pH between 6.91 to 8.18. These values were still preferable for coral growth and developments, and still in the range of the criterias established by the Ministry for Population and Environment (KLH) for various interests. Variation of hydrological conditions were not the cause of coral damage in the waters of Talise Island. Keywords : monitoring, hydrology, coral reef, Talise island, North Sulawesi   ABSTRAK Pemantauan kondisi hidrologi di perairan  Pulau Talise, Sulawesi Utara telah dilakukan pada bulan Juli dan Oktober 2009. Hasilnya menunjukkan suhu berkisar antara 28,85-30,70 oC, salinitas antara 33,0-34,0 o/oo, kecerahan antara tampak dasar td-24 m, oksigen terlarut antara 5,05-6,01 ppm, zat hara fosfat antara 0,015-0,056 mg/l,  nitrat antara 0,003-0,020 mg/l dan pH antara 6,91-8,18. Nilai-nilai tersebut masih baik untuk pertumbuhan dan perkembangan karang, dan masih sesuai dengan kriteria yang ditetapkan oleh Kementerian Kependudukan dan Lingkungan Hidup (KLH) untuk berbagai kepentingan. Variasi kondisi hidrologi bukan merupakan penyebab kerusakan karang di perairan Pulau Talise. Kata kunci : pemantauan, hidrologi, terumbu karang, Pulau Talise, Sulawesi Utara